2019
DOI: 10.5194/acp-19-9253-2019
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Arctic stratospheric ozone on surface climate in CCMI models

Abstract: Abstract. The Northern Hemisphere and tropical circulation response to interannual variability in Arctic stratospheric ozone is analyzed in a set of the latest model simulations archived for the Chemistry-Climate Model Initiative (CCMI) project. All models simulate a connection between ozone variability and temperature/geopotential height in the lower stratosphere similar to that observed. A connection between Arctic ozone variability and polar cap surface air pressure is also found, but additional statistical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…The CCMI models used in this study are listed in Table 1. Harari et al (2019) showed that each of these models simulate surface temperature variability in the Nino3.4 region similar to that observed.…”
supporting
confidence: 75%
“…The CCMI models used in this study are listed in Table 1. Harari et al (2019) showed that each of these models simulate surface temperature variability in the Nino3.4 region similar to that observed.…”
supporting
confidence: 75%
“…The above-mentioned studies mostly focused on the impact of stratospheric polar vortex changes on the weather and climate over continents with a large population or the Atlantic Ocean, where the NAO teleconnection pattern is active. Furthermore, an increasing number of studies have confirmed the potential connections between the stratospheric polar vortex and the climate over the North Pacific Ocean [28][29][30][31]. Recently, Xie et al [28] found that Arctic stratospheric ozone (ASO) variation could affect El Niño-Southern Oscillation (ENSO) events after 20 months by modulating the atmosphere-ocean feedback over the North Pacific Ocean, i.e., ASO affects North Pacific Oscillation (NPO) and then induces a Victoria Mode (VM) anomaly, which is closely related to ENSO events.…”
Section: Introductionmentioning
confidence: 97%
“…Even without Arctic ozone loss, stratospheric dynamical variability has also been shown to influence surface conditions in early studies (Ayarzagüena & Serrano, 2009;Black & McDaniel, 2007;Hardiman et al, 2011). A connection between Arctic ozone variability and extratropical surface is probably mediated by the dynamical variability that typically drives the anomalous ozone concentrations rather than the opposite (Harari et al, 2019). Manney et al (2020) recently reported on the chemical processes during the extreme ozone loss in March 2020; however, the predictability of the extreme ozone loss in March 2020 (andin March 1997 and and of the subsequent surface impact has still not been explored.…”
Section: Introductionmentioning
confidence: 99%